HUBUNGAN ANTARA SELF ESTEEM DENGAN SOCIAL COMPARISON PADA REMAJA DI SMP X AMBARAWA KABUPATEN PRINGSEWU - Putra, Rehan Dauly; Rima Wilantika (Jurnal Psimawa : Diskursus Ilmu Psikologi dan Pendidikan, 2025)
Teenagers have a desire to compare themselves with others so that they always compare themselves to their peers and social environment. Social comparison occurs when they evaluate and determine themselves based on perceptions of themselves compared to others. One of the factors that influence social comparison is self esteem. This study aims to determine the correlation between self esteem and social comparison in adolescents at Junior High School X Ambarawa, Pringsewu Regency. The approach used in this study is quantitative with sampling techniques using cluster random sampling. The population of this study consisted of class X students at Junior High School X Ambarawa, Pringsewu Regency, which amounted to 840, with a sample of 204 students. The results of data analysis showed a highly significant positive correlation between self esteem and social comparison in junior high school adolescents, with a product moment correlation value of r = 0.551 and a significance value of p = 0.000 (p < 0.01). This means that the higher the self esteem, the higher the social comparison done by adolescents.